PERLINDUNGAN HUKUM TERHADAP PASIEN SEBAGAI KONSUMEN JASA PELAYANAN KESEHATAN - Asram AT Jadda (Madani Legal Review, 2017)
This research is about “legal protection for patient as health service consumer”. It belongs ti the juridical normative research, describing the provisions in law and regulation, in relation to the fact in the field, then conducting analysis by comparing the existing ideal values in law and regulation with the fact in the field. Therefore, it conducted library research supported with field research provides knowledge on the difference between as sollen and das sein.The research conducts document study and field research. Document study is data collecting from bibliography such as law and regulation, book, magazine, document, and also articles relevant with this research tipic. Field research collects data by direct observation in the field to look for the relevant information througt direct using interview guideline and questionnaire. Respondents are selected using purposive sampling method.Generally, legal protection for medical patient in Faisal Islamic Medical Centre (RSI Faisal) Ujung Pandang is still low. It can be shown from the fact that medical action which may cause patient’s health hazard or death are still untouched by law. Poor protection can also be seen from the difficulty to ask hospital/doctor/ medical personnel to be responsible for patient heath condition hazard or death because of doctor/medical personnel malpractice. Poor protection to the patien is caused by there is no equality before the law between doctor/medical personnel and patient. Poor protection to the patient also caused by the absence of malpractice act which is supposed to be the base for settling malpractice committed doctor/medical personnel.